Satellite mapping in cities and below cities: how good is it now? - Hancock, Craig; Zhang, Penghe; Lau, Lawrence; Roberts, Gethin Wyn; de Ligt, Huib (ICE Publishing, 2016)
Global navigation satellite systems (GNSS) have existed since the launch of the US global positioning system constellation in 1978. There is an increasing need for better maps in the digital age, particularly for buried utilities. One of the most convenient methods for creating accurate maps is the use of navigation satellites for positioning. However, built-up urban areas are not ideal for the use of this positioning technology. This paper provides an update on the situation regarding GNSS and assesses how new satellites and signals are contributing to better positioning availability by carrying out a test in a controlled environment. The results show that using combined satellite systems improves availability in urban canyons in some cases, but not in all scenarios. In addition, pipeline mapping technology has been tested and been shown to be an effective means of mapping pipes deep under the ground over short distances.